A Review of Strategic Human Resources Management in Organization - Hermansyah Hermansyah; Martinus Tukiran; Erna Herlina; Muhammad Tito Andrianto (Budapest International Research and Critics University, 2022)
This article aims to review three recent articles on the topic of strategic human resource management and discuss their relationship to some theories and concepts. The study used a qualitative descriptive method by reviewing literature from SCOPUS indexed journals to ensure the availability of research related to strategic human resource management. The results of the finding shown that Researchers often link SHRM with company performance, human capital and competitive advantage by using several theoretical approaches, including the resource-based view (RBV), social exchange theory (SET), and human capital theories. The reviewed articles treat the topic of SHRM differently, but, on the whole, they identify gaps that exist in SHRM research and demonstrate the importance of aligning HR practices vertically and horizontally.